Blastomycosis: A Rare Cause of Pleural Effusion, Diagnosed on Cytology - Mayur Ambekar; Archana C. Buch; Mangesh Londhe (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Among fungal infections, fungal empyema (FE) is rare and has significant mortality. Microscopic examination of the pleural fluid plays an essential role in its diagnosis. Since pleural fluid can be obtained easily as a bedside procedure, yielding significant diagnostic material, other invasive and expensive procedures can be avoided. The fungal elements identified in FE on microscopy can be yeasts, filamentous fungi, and dimorphic fungi. The morphology of spherical, thick-walled yeast cells showing broad-based budding is commonly seen in blastomycosis, coccidioidomycosis, and cryptococcosis. Though microbiological tests remain the gold standard, pleural fluid cytology with various special stains can be used as a rapid, reliable test for diagnosis. This has the advantages of prompt diagnosis, minimum expertise, and cost-effectiveness. We present a case of a 75-year-old male who presented with bilateral pleural effusion, the cytology of which revealed blastomycosis.